Reformasi Pengelolaan Royalti Musik: Menuju Sistem yang Adil dan Transparan bagi Pencipta Lagu - Sebastian Siitumorang; Tomy Michael (Jurnal Multidisiplin Ibrahimy, 2025)
Song and music copyright royalty management is a crucial aspect of protecting intellectual property rights, particularly for creators. Although Indonesia has a legal basis through Law Number 28 of 2014 and Government Regulation Number 56 of 2021, practice still faces various obstacles such as low transparency, weak data collection systems, and a lack of business awareness. This research uses a normative juridical approach by analysing regulations, policy effectiveness, and the role of the National Collective Management Institute (LMKN). The study results indicate a significant need for comprehensive reform, encompassing at least three approaches: institutional strengthening with human resources with integrity and the use of technologies such as blockchain; increased digital literacy; synergy between stakeholders; and regulatory improvements accompanied by law enforcement. These reforms are expected to create a fair, efficient, and sustainable royalty management system to support the growth of the national music industry.